VARIASI FAKTOR EKSPOSI PADA PEMERIKSAAN SCHEDEL PROYEKSI ANTERIOR POSTERIOR UNTUK HASIL RADIOGRAFI YANG MAKSIMAL DI RUMAH SAKIT AL ISLAM BANDUNG: Variation of Exposure Factors on Schedel Examination using Anterior Posterior Projection to Maximize Radiographs Quality at Al Islam Hospital of Bandung - Oktarina Damayanti; Leny A Anggraeni; Surdiyah Asri Ningrum (JURNAL TERAS KESEHATAN, 2020)
The head is an examination that is often done at each hospital, especially Posterior Anterior projection. The quality of the results of a good picture of contrast, density and detail are needed so that the exposure factor will be very influential on the head examination. The study was conducted at Al Islam Hospital in Bandung using the head phantom. Variations in kV and mAs in this study were AP projections with 64 kV and 11.2 mAs, AP schemes with 72 kV and 14.2 mAs, AP heads with 80 kV and 12.6 mAs, AP heads with 88 kV and 14, 2 mAs and AP head radiographs with 96 kV and 16.0 mAs. The maximum exposure factor value on the head phantom in anteroposterior projections based on the data is that the respondent's value has changed and only one is the same or similar from the respondent's perspective, the use of kV 64 and mAs 11.2 has a density value of the ten respondents by 94%, the value of in contrast to the ten respondents by 68%, the sharpness value of the ten respondents by 74%, and the detailed value of the ten respondents by 74%. In the use of kV 72 and mAs 14.2, the density value of the ten respondents was 42%, the contrast value of the ten respondents was 44%, the sharpness value of the ten respondents was 38%, and the retail value of the ten respondents was 38%. The use of kV 80 and mAs 12.6 has a density value of the ten respondents of 56%, the contrast value of the ten respondents by 44%, the sharpness value of the ten respondents by 40%, and the retail value of the ten respondents by 40%. In the use of kV 88 and mAs 14.2, the density value of the ten respondents was 78%, the contrast value of the ten respondents was 64%, the sharpness value of the ten respondents was 64%, and the retail value of the ten respondents was 64%. In the use of kV 96 and mAs 16.0, the density value of the ten respondents was 78%, the contrast value of the ten respondents was 76%, the sharpness value of the ten respondents was 64%, and the retail value of the ten respondents was 80%. According to the evaluation of the ten respondents expose at Al Islam Hospital Bandung, the results of the first radiograph with the exposure factor kV 64 and mAs 11.2 had the highest value. And the lowest index value of each respondent is the exposure factor kV 72 and mAs 14.2.